The Influence of Intellectual Capital, Good Corporate Governance, Green Accounting, Business Risk, and Audit Quality on the Value of Energy Sector Companies - Zaina Fiah; Nora Susanti; Yesmira Syamra (Journal of Creative Power and Ambition (JCPA), 2026)
The research results indicate that: (1) intellectual capital does not have a significant effect on firm value, with a t-statistic of 1.952160 and a probability value of 0.0666 (> 0.05); (2) Good Corporate Governance does not have a significant effect on firm value, with a t-statistic of 1.143517 and a probability value of 0.06 (> 0.05); (3) Green Accounting has a significant effect on firm value, with a t-statistic of 1.974321 and a probability value of 0.0323 (< 0.05); (4) business risk does not have a significant effect on firm value, with a t-statistic of -0.623606 and a probability value of 1.14 (> 0.05); and (5) audit quality has a significant effect on firm value, with a t-statistic of 1.032861 and a probability value of 0.0053 (< 0.05). Thus, of the five independent variables tested, only intellectual capital, green accounting, and audit quality were proven to have a significant effect on firm value.